The effect of the mode of delivery on neonatal thyroid function - BEREKET, ABDULLAH; ÖZEK, EREN; BİLGEN, HÜLYA SELVA; DEMİRCİOĞLU, SERAP (TAYLOR & FRANCIS LTD, 2007)
Background. We aimed to investigate the effect of the mode of delivery and the type of anesthesia on postnatal thyroxine (T4), free T4 (f-T4) and thyroid-stimulating hormone (TSH) in a large number of healthy full-term neonates. Methods. Serum samples for T4, TSH and f-T4 were drawn from neonates at the time of discharge (postnatal days 1-7) in a pilot thyroid-screening program. Six hundred and thirty-eight neonates were grouped as: vaginal delivery (VD; 332), elective cesarean section (elective C/S; 252) and emergency cesarean section (emergency C/S; 54). The elective C/S group was subdivided into local and general anesthesia groups to investigate the influence of the type of anesthesia used on thyroid function. Results. Mean +/- SD serum T4, TSH and f-T4 levels tended to be higher in the VD group compared to the elective C/S group at almost all time points. However the differences did not reach statistical significance, except for the T4 levels at postnatal day 3 in the VD group, which was higher (195.6 +/- 37.3 nmol/L) compared to the elective C/S group (160.9 +/- 34.8 nmol/L) (p < 0.001). The only difference in the anesthesia groups was the slightly higher f-T4 levels from postnatal day 4 in the local anesthesia group compared to the general anesthesia group. Conclusions. The mode of delivery or type of anesthesia does not have considerable influence on postnatal thyroid functions in the neonates, although minor differences exist. Therefore similar cut-off values can be used for thyroid screening of term newborns regardless of the mode of delivery or type of anesthesia used.
Keywords: anesthesia; mode of delivery; neonates; thyroid function tests; thyroid screening; CORD-BLOOD; THYROTROPIN; HORMONES; RELEASE